Altered platelet morphological parameters in patients with retinal vein occlusion - Yilmaz, T; Yilmaz, A (European review for medical and pharmacological sciences, 2016)
The purpose of this work was to investigate whether platelet morphology or functions are altered in retinal vein occlusion (RVO) patients. Eighty-three patients with a RVO and eighty-five healthy subjects were included in this prospective study. RVO was diagnosed by ophthalmic fundus examination, and complete ophthalmic evaluations of both eyes were performed. The platelet large cell ratio (PLCR), platelet distribution width (PDW), mean platelet volume (MPV), platelet crit (PCT), and platelet count were determined for each participant. The MPV, PDW and PLCR were significantly higher in the RVO group than in the control group (MPV: 8.26 ± 1.22 fL vs. 7.41 ± 0.69 fL, respectively, p = 0.006; PDW: 13.43 ± 1.75% vs. 12.19 ± 1.51%, respectively, p = 0.0022; and PLCR: 30.62 ± 4.65% vs. 28.59 ± 4.18%, respectively, p = 0.003). There were no significant differences in the PCT or platelet count between the two groups (253.76 ± 70.87 x 103/µl vs. 248.96 ± 62.44 x 103/µl, respectively p > 0.05; and PCT: 0.24 ± 0.07 % vs. 0.27 ± 0.06%, respectively, p > 0.05). We observed that the platelets RVO patients exhibit morphological evidence of hyperreactivity (e.g., a higher MPV, PDW and PLCR). Also, larger platelets are hemostatically more active than small ones and an increased proportion of large platelets is a risk factor for developing RVO.